Use of Pralsetinib as Neoadjuvant Therapy for Non-Small Cell Lung Cancer Patient With RET Rearrangement - Zhou, Ning; Li, Tong; Liang, Maoli; Ren, Fan; Ni, Hong; Liu, Wei; Shi, Tao; Xu, Dongbo; Chen, Qiusong; Yu, Haonan; Song, Zuoqing; Zu, Lingling; et al. (Frontiers in Oncology, 2022)
RET rearrangements are rare, and occur in 1%-2% of all non-small cell lung cancer (NSCLC) patients. Pralsetinib has a significant anti-tumor effect in patients with advanced NSCLC and a RET rearrangement. Previous studies have confirmed the efficiency of neoadjuvant target therapy for NSCLC. Herein we present a case involving a female patient who was diagnosed with stage IIIA lung adenocarcinoma and harbored a KIF5B-RET rearrangement based on next-generation sequencing. Radiologic downstaging was indicated after pralsetinib treatment. Therefore, a right lower lobectomy and systemic lymphadenectomy were successfully performed. The postoperative pathologic results revealed a response rate of 74% for primary tumor and no residual viable tumor cells were observed in lymph nodes. The tumor, nodes, and metastases (TNM) stage was ypT1cN1M0. The tumor micro-environment (TME) of the primary tumor was also assessed.